(untitled) (Research, Society and Development, 2021)
Objective: To evaluate the impact of Oriental Therapeutic Exercises on stress biomarkers and contributions to university students. Method: Mixed sequential explanatory study carried out with 19 university students between and December 2019. Sociodemographic data, measurements of salivary alpha amylase and heart rate variability were collected before and after the exercises and a focus group was performed in a single session. Results: The majority were women, average of 22 years old, white, non-heterosexual, without religion and children, did not exercise paid activity, lived in republics, gross monthly family income of two prices and depended financially on the family. They were the first members of the family to enter a public university, assisted by the student assistance program, in the final stage of integral courses and scoring with the choice. The practice of Oriental Therapeutic Exercises influenced the increase in heart rate variability, helping to relax. Contributions to health promotion and the construction of a social support network. Conclusion: There is a demand for institutional actions, such as an offer of integrative and complementary practices, which favor the promotion of health and social support of students. The studied practice comprises an innovative method guided by the comprehensiveness and expanded health needs of university students.